Storia naturale dell’infiammazione allergica - Tosca, Maria Angela; Ciprandi, Giorgio (Farmeconomia. Health economics and therapeutic pathways, 2002)
Allergic pathologies are the most common immunologic diseases and their prevalence and severity show a constantly increasing trend in industrialized countries. The present article presents some recent epidemiological data, the natural development of the allergic inflammation and its pathophysiology, focusing on the recent concept of a “minimal persistent inflammation”, with particular regard to its long term treatment with antiallergic drugs. In fact, according to the most recent interpretations, allergy has to be considered as a complex phenomenon, characterized by a inflammatory response to allergenic stimuli. The complicated interrelation between cells, cytokines and affected structures is described. Very often allergic diseases of the upper airways are associated with and complicate asthma, and data that support the benefits of treating these diseases as a whole are presented. Long-term treatment of allergies with antiflogistic/antiallergic molecules is capable of reducing tissutal damage, besides improving the quality of life of the patient and lowering the frequency of acute episodes. The chronic treatment with antiallergic drugs appears to be favorable also from a pharmacoeconomical point of view, as it is associated with a reduction of overall pharmaceutical expenses and of lost working/school days, as well as determining an improved quality of life for the patient and its relatives, particularly in pediatric age. The management of the allergic patient has always to be approached with an integrated multidisciplinary attitude, in which the efforts tend to the identification of all concurrent diseases, because the optimal treatment may be achieved only with the recognition and the resolution of all underlying diseases.